Cell wall response of field grown Populus to Septoria infection - Bryant, Nathan; Muchero, Wellington; Weber, Rachel A.; Barros, Jaime; Chen, Jin-Gui; Tschaplinski, Timothy J.; Pu, Yunqiao; Ragauskas, Arthur J. (Frontiers in Plant Science, 2023)
Biomass yield is one of the key factors influencing the viability of biofuel feedstocks such as Populus. This can be detrimentally impacted in part by infection by fungal pathogens such as Sphaerulina musiva (Septoria), which is known to spread rapidly and cause symptoms such as stem canker. This study investigated the long-term impacts of Septoria infection on field-grown poplar, with a particular focus on lignin. Fourier-transform infrared spectroscopy and subsequent principal component analysis revealed that infected and border (along the periderm) tissue were similar and could be distinguished from the non-infected (healthy) tissue. Nuclear magnetic resonance results indicated the general trend that infected tissue had a higher syringyl:guaiacyl ratio and lower p-hydroxybenzoate content than the healthy tissues from the same genotype. Finally, Klason lignin content in the infected and/or border tissue was shown to be higher than healthy tissue, which is consistent with previous observations of periderm development and metabolite profiling. These results provide insights on the response of Populus wood characteristics to Septoria infection, especially between healthy and infected tissue within the same genotype.